Lysosomes and α-synuclein form a dangerous duet leading to neuronal cell death - Bourdenx, Mathieu; Bezard, Erwan; Dehay, Benjamin (Frontiers in Neuroanatomy, 2014)
Neurodegenerative diseases are (i) characterized by a selective neuronal vulnerability to degeneration in specific brain regions; and (ii) likely to be caused by disease-specific protein misfolding. Parkinson’s disease (PD) is characterized by the presence of intraneuronal proteinacious cytoplasmic inclusions, called Lewy Bodies (LB). α-Synuclein, an aggregation prone protein, has been identified as a major protein component of LB and the causative for autosomal dominant PD. Lysosomes are responsible for the clearance of long-lived proteins, such as α-synuclein, and for the removal of old or damaged organelles, such as mitochondria. Interestingly, PD-linked α-synuclein mutants and dopamine-modified wild-type α-synuclein block its own degradation, which result in insufficient clearance, leading to its aggregation and cell toxicity. Moreover, both lysosomes and lysosomal proteases have been found to be involved in the activation of certain cell death pathways. Interestingly, lysosomal alterations are observed in the brains of patients suffering from sporadic PD and also in toxic and genetic rodent models of PD-related neurodegeneration. All these events have unraveled a causal link between lysosomal impairment, α-synuclein accumulation, and neurotoxicity. In this review, we emphasize the pathophysiological mechanisms connecting α-synuclein and lysosomal dysfunction in neuronal cell death.